Bagaimanakah Preferensi Mahasiswa Terhadap Magang? Kajian di Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman - Shalsabila, Rakhmelia Nur; Suharno, Suharno; Fauzi, Pahrul (Jurnal Ecodemica: Jurnal Ekonomi, Manajemen, dan Bisnis, 2023)
Student preferences for participating in MBKM internships can be taken into consideration by companies to find out student interests and can support student careers in the future. This study aims to analyze student preferences for the MBKM internship at FEB Unsoed. The method used is Logistic Regression or Logistics Model Analysis (LOGIT). This research is quantitative. The data used are primary and secondary data. Sampling using proportionate stratified random sampling technique. Based on the research results, the independent variable that has the most influence on the dependent variable is the location of the company (1.687) that the farther the location of the company from the place of residence will increase the probability of students participating in internships by 1.687 times greater than students who choose not to take part in MBKM internships, followed by variables incentives (1,500), and company brand variables (1,395). This shows that company location, incentives, and company brand influence students' preferences to take part in MBKM internships. Keyword: Student Preference, MBKM Internship,  Incentives, Location, Brand Company